Memprediksi Penjualan Pada Toko Hanifah Metode C.45 - Muhammad Afdhal; Vicky Ariandi; Rita Rita (Prodi Sistem Informasi Universitas Dharma Andalas, 2022)
Drug stocks in pharmacies are important information for the sales process. The existing stock is not in accordance with the needs of consumers, the distribution of drugs that are less needed in the stock will cause losses because the drug has expired due to too long stored in the warehouse. Another problem is that obat cannot predict drugs that are needed a lot, to overcome these problems needed a prediction system. These problems can be solved by the decision tree method for the prediction of drug supplies. The concept of the Decision Tree Algorithm is to convert data into decision trees and decision rules. System development with Waterfall model, using PHP programming language, My SQL database, system design using object oriented approach, system testing using Black Box for functionality test, validity testing with rapid miner tools. The result of the development of the system is a prediction of drug sales at pharmacies. The result of black-box testing is that all developed systems work properly. The results of the validity test by comparing the old system with the new system with the rapid miner, using 30 transaction samples the accuracy is 89% which means the system has good performance.